1995
DOI: 10.1128/aac.39.8.1779
|View full text |Cite
|
Sign up to set email alerts
|

Antagonistic interactions between azoles and amphotericin B with yeasts depend on azole lipophilia for special test conditions in vitro

Abstract: The interactions of the azole antifungal agents fluconazole, itraconazole, ketoconazole, or miconazole with amphotericin B (AmB) in their effect on Candida albicans were investigated. These four azoles antagonized the fungistatic activity of AmB at sub-MICs if both substances acted simultaneously. This coincubation test was primarily developed to observe the azole-mediated demethylase inhibition quantitatively by bioassay. Interestingly, the occurrence of azole-AmB antagonism depended on azole lipophilia if sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
1
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 19 publications
2
47
1
1
Order By: Relevance
“…These results are in agreement with the described activity of penconazol as an inhibitor of ergosterol biosynthesis in fungi (K oller, 1992). In fact, cells may accumulate ergosterol reserves in the membranes, and the azole-induced depletion of these reserves may take some hours (Scheven and Schwegler, 1995). This would allow growth to proceed normally for some time, after which it would arrest.…”
Section: Resultsmentioning
confidence: 99%
“…These results are in agreement with the described activity of penconazol as an inhibitor of ergosterol biosynthesis in fungi (K oller, 1992). In fact, cells may accumulate ergosterol reserves in the membranes, and the azole-induced depletion of these reserves may take some hours (Scheven and Schwegler, 1995). This would allow growth to proceed normally for some time, after which it would arrest.…”
Section: Resultsmentioning
confidence: 99%
“…Antagonism among antifungal agents might occur in one of several ways. (i) Direct antifungal action at the same site results in decreased ability of other agents to exert their competitive effects on that site or at an altered target, as proposed for the azoles and amphotericin B (31,49,182,183,185,186,203). Azoles block the synthesis of ergosterol in the fungal cell membrane and may thus render amphotericin B inactive, since this agent exerts its activity by binding to ergosterol in the cell membrane.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
“…(ii) Adsorption to the cell surface by one agent inhibits binding of another antifungal agent to its target site of activity. This mechanism is proposed for lipophilic azoles (such as itraconazole and ketoconazole) which may adsorb to the fungal cell surface and inhibit binding of amphotericin B to fungal cell membrane sterols (183,185). (iii) Modification of a target upon exposure to an antifungal agent occurs that renders the pathogen less susceptible to the effects of other antifungals.…”
Section: Mechanisms Of Interactions For the Antifungal Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several investigators have found synergistic interactions by simultaneous exposure of C. albicans to azoles and AmB (13,30). One group, on the other hand, described antagonisms with preexposures of Candida to the more lipophilic azoles, such as itraconazole, but not to fluconazole (31,32).…”
mentioning
confidence: 99%